PENDEKATAN SOSIOSEMANTIK-LEKSIKAL DALAM PERISTILAHAN PERKEBUNAN TEH - Wiwin Erni Siti Nurlina; Lili Dahliani (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2022)
The communication of science must be clear so that the concept of science can be understood clearly and precisely. The concept of plantation science can be in the form of a term. Many of the terms in the tea plantation sector are adopted from regional languages, one of which is Sundanese. In this paper, the terminology of the tea plantation field which is often used by Sundanese people is examined. To understand the meaning of these terms, a sociosemantic- lexical approach is used. The studying of meaning on the lingual form of the term includes its meaning related to the meaning of the socio-cultural view of the Sundanese people. The meaning components contained in the term concerned are studied lexically. The method is descriptive qualitative, with the technique of sorting the meaning components and categories. The meaning component consists of a shared meaning component and a specific meaning component that can be identified through a componential analysis. By using sociosemantic-lexical approach, the meaning of the term concerned can be clearly and precisely known. Based on the category, the term plantation is categorized into (i) noun (thing), such as peko, manjing; (ii) verbs (activity) such as ngabentang, mupul, ngodok; and (iii) adjectives (state), such as nyeupan, hiaten. Based on the semantic analysis, the correct meaning of the term will be revealed.The components of social meaning that exist are togetherness and respect.Komunikasi ilmu haruslah jelas agar konsep dapat dipahami dengan pasti. Konsep ilmu perkebunan dapat berupaistilah. Peristilahan pada bidang perkebunan banyak yang diangkat dari bahasa daerah, salah satunya Bahasa Sunda. Pada tulisan ini dikaji peristilahan bidang perkebunan teh yang sering digunakan oleh masyarakat yang berasal dari bahasa Sunda. Untuk memahami makna peristilahan tersebut digunakan pendekatan sosiosemantik-leksikal. Maksudnya, telaah makna pada bentuk lingual istilah dikaji maknanya dengan melibatkan makna pandangan sosial budaya dari masyarakat Sunda. Komponen makna yang terkandung pada istilah yang bersangkutan dikaji secara leksikal. Metode yang digunakan ialah deskriptif kualitatif, dengan teknik pilah komponen makna dan pilah kategori. Komponen makna tersebut terdisi atas komponen makna bersama dan komponen makna spesifik yang dapat diketahu melalui analisis komponen makna (componential analysis). Dengan pendekatan sosiosemantik-leksikal tersebut, dapat diketahui secara jelas dan tepat makna dari istilah yang bersangkutan. Berdasarkan kategorinya, istilah perkebunan teh ada yang berjenis kategori (i) nomina (benda), seperti peko, manjing; (ii) verba (aktivitas) seperti ngabentang, mupul, ngodok; dan (iii) adjektiva (keadaan), seperti nyeupan, hiaten. Berdasarkan analisis semantiknya, istilah akan terkuak ketepatan maknanya. Komponen makna sosial yang ada yaitu kebersamaan dan rasa hormat.